Czy Polska powinna pomóc Grecji? Relacja z debaty polityczno-ekonomicznej 2010-2012 - Kropiwnicki, Jerzy (Annales. Etyka w Życiu Gospodarczym, 2015)
This question raised emotions in Poland in 2010-2012. They began with the statement by the Prime Minister in March 2010 that Poland was ready to participate in a program of assistance to Greece. It evoked very strong reactions – not only in debates in conferences halls and in professional journals, but also in the tabloids and on TV and the radio. It was not only politicians and academic experts in economics who took part in those debates, but also the editors of the popular newspapers. The arguments “for” and “against” of different character were raised. Those “for” advocated on the grounds of the principle of solidarity, but also on the grounds of the principle of subsidiarity – arguing that the burden of the problem is beyond the possibilities of Greece to solve herself. They also raised the necessity to defend the endangered common good – the European Union, and argued that prudence advises earning reciprocation in case Poland meets problems in the future. Those “against” pointed out that it was immoral to expect that a much poorer society was expected to assist one that was better off. Another point raised in the debate was that it was the Greeks themselves, both the political elites and the society as such, who were guilty of creating Greece’s problems. The main problem was the institutions of the welfare state, developed beyond the capacities of the country. But there were also some more shocking reasons of the Greek economic problems – and among them massive tax-avoidance, unauthorized social benefits payments, and transfers of incomes to foreign bank accounts. There was also the manipulation of statistical data or even their falsification, by (or with the approval of) the government. Some participants in the debate raised the problem Greek frauds and social dysfunctions being very well known to the EU authorities, the partners of Greece in EMU and by the German and French commercial banks. So – following from the above – Poland should not participate in any programs of assistance to Greece, and the burden of the problem should rest on those who had been responsible for it or who had tolerated its growth because of expected profits. In other words: Greek society, its political elites and the banks and those countries that had tolerated the developments. The debate ended in Poland when the member-states of the EMU decided that they would take decisions concerning Greece within their own group. And it was decided that “troika” – representatives of the European Commission, ECB and IMF – would decide on the size of the assistance and of the conditions. Poland, as a member of the IMF, does in fact participate in the costs of the assistance programs, but this fact does not evoke great emotions.